2022
DOI: 10.3389/fonc.2022.791620
|View full text |Cite
|
Sign up to set email alerts
|

Is Lymph Node Dissection Necessary During Radical Nephroureterectomy for Clinically Node-Negative Upper Tract Urothelial Carcinoma? A Multi-Institutional Study

Abstract: PurposeThis study aimed to compare the oncological outcomes of patients with upper tract urothelial carcinoma (UTUC) without clinical lymph node metastasis (cN0) undergoing lymph node dissection (LND) during radical nephroureterectomy (NU).MethodsFrom the updated data of the Taiwan UTUC Collaboration Group, a total of 2726 UTUC patients were identified. We only include patients with ≥ pT2 stage and enrolled 658 patients. The Kaplan–Meier estimator and Cox proportional hazards model were used to analyze overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…On the other hand, some retrospective studies showed that there was no survival difference between cN0 patients who did and did not undergo LND, but the subgroup analyses according to the number of removed LNs were not performed [ 19 , 20 ]. One of the multicenter retrospective analyses demonstrated that in cN0 muscle-invasive UTUC (≥pT2 stage) LND did not provide a survival benefit when compared to no LND [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, some retrospective studies showed that there was no survival difference between cN0 patients who did and did not undergo LND, but the subgroup analyses according to the number of removed LNs were not performed [ 19 , 20 ]. One of the multicenter retrospective analyses demonstrated that in cN0 muscle-invasive UTUC (≥pT2 stage) LND did not provide a survival benefit when compared to no LND [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some retrospective studies showed that there was no survival difference between cN0 patients who did and did not undergo LND, but the subgroup analyses according to the number of removed LNs were not performed [ 19 , 20 ]. One of the multicenter retrospective analyses demonstrated that in cN0 muscle-invasive UTUC (≥pT2 stage) LND did not provide a survival benefit when compared to no LND [ 20 ]. The lack of benefit from LND observed in many retrospective studies might be due to the incompleteness of the dissection and the inclusion of cNx or even cN1 patients “incorrectly” classified as pNx due to the lack of histopathological examination.…”
Section: Discussionmentioning
confidence: 99%
“…In 30-40% of radical NU surgeries, a suspected lymph node is visible. However, the benefits of lymph node dissection (LND) for node-negative (cN0) UTUC have not yet been established [62]. Notably, while LND improves pathological staging, the updated EAU guidelines do not recommend LND for cT1N0 disease [34].…”
Section: Oncological Considerationsmentioning
confidence: 99%
“…The authors showed inferior DFS (hazard ratio 2.40, P < 0.001) and CSS (hazard ratio 2.39, P < 0.001) in pN+ patients compared with pN0 patients using multivariable Cox regression analysis [27]. As shown in Table 1, compared with pN0, the negative prognostic impact of pN+ with regard to DFS and CSS has been supported by several studies, such as Burger et al [28] in 2011 (hazard ratio for DFS: 2.0, hazard ratio for CSS: 2.1, n = 785), Mason et al [29] in 2012 (hazard ratio for DFS: 2.01, hazard ratio for CSS: 2.94, n = 1029), Ikeda et al in 2017 (hazard ratio for DFS: 3.25, hazard ratio for CSS: 3.56, n = 399) [30], Li et al in 2021 (hazard ratio for CSS: 3.08, hazard ratio for CSS: 4.41, n = 1340) [31], Hsieh et al [33] in 2022 (hazard ratio for CSS: 2.01, n = 520) [32], Lee et al [34 ▪▪ ] in 2022 ( P < 0.001 in DFS and P = 0.01 in CSS, n = 658), and Hakimi et al in 2022 (HR for DFS: 1.80, HR for CSS: 2.74, n = 877). In addition, two studies showed that pN+ was associated with worse OS in UTUC patients compared to pN0; for example, Mason et al in 2012 (HR for OS: 2.70, n = 1029) and Hakimi et al in 2022 (hazard ratio for OS: 2.77, n = 877) [29,31].…”
Section: Evidence Synthesismentioning
confidence: 99%